Índices antropométricos e estilo de vida associados ao risco cardiovascular e síndrome metabólica em adolescentes de Palmas (TO): estudo Erica - Silva, Kellen Cristine (Universidade Federal de Viçosa, 2020)
Objective: To evaluate cardiovascular risk markers (CRM) and metabolic syndrome (MetS) and their relationship with anthropometric indices and adolescent lifestyle in a sample selected by complex sampling. Methods: Cross-sectional study performed with a subsample (n = 1069; 12 until 17 years) from Study of Cardiovascular Risks in Adolescents (ERICA) from Palmas (TO). The study units were selected by stratification and clustering in three stages (1st schools, 2nd shifts and years and 3rd classes). Socioeconomic, demographic, food consumption, physical activity, sleep, smoking, anthropometric, lipid, glycaemic and blood pressure profile data were collected. The impact of the complex sampling on production of CRM means and proportions, and their respective standard errors and 95% confidence interval (CI), was observed comparing results under two perspectives: with and without sample weights incorporation in data analysis. From anthropometry, body mass index (BMI), waist circumference (WC), waist-height ratio (WHR), conicity index (CoI), body shape index (BSI), BSI adjusted for adolescents (BSI-adjusted) and body roundness index (BRI) were calculated. The reliability of these indices to predict individual MRC and MetS was obtained by constructing Receiver Operating Characteristics (ROC) curves and calculating Area Under Curves (AUC). Unhealthy lifestyle behaviour (ULB) score was constructed based on overweight, physical inactivity, low fruit and vegetable intake and insufficient sleep time. Crude and adjusted prevalence ratios (PR) were calculated by Poisson regressions with robust variance to identify the association between high blood pressure and ULB score, and between sixteen ULB combinations. ROC curves and regressions were produced considering complex sampling. Results: From overall adolescents evaluated, most were girls (n = 570, 53.32%) and students from public schools (n = 855, 89.05%). Overall, standard errors and 95%CI length were higher considering the complex sampling. Limited reliability of anthropometric indices was observed to predict individual CRM, especially in girls. For MetS, all indices showed very good to excellent reliability. In both sexes, CoI, BSI, BSI-adjusted and BRI show reliability equal to or less than BMI, WC and WHR. Less than 5% of adolescents are free of any ULB. Prevalence of high BP was 11.41% (8.39-15.34), overweight 17.09% (13.30-21.69), physical inactivity 62.76% (57.96-67.33), low consumption of fruits and vegetables 77.61% (72.76-81.81) and insufficient sleep 50.20% (37.64-62.74). Adolescents with ≥ 3 ULB have more prevalence of high BP. Individual overweight or combined with any other behavior was the only risk factor for high BP (PR = 3.31, 95% CI 2.29-4.77). Conclusions: Ignoring sample weights in statistical data analysis may compromise results validity, so incorporating them when using data from complex samples should be part of the analysis routine. Despite limited reliability, among anthropometric indices analysed, BMI, WC and WHR are still the best choice to predict individual MRC and MetS in the adolescence. For MetS screening, we recommend the use of WHR ≥0.55 due to the ease of measurement and interpretation in Brazilian adolescents. ULB co-occurrence is a reality in this population and a risk factor for high BP, and overweight is a major contributor this association.